TOUCHING THE FINISH LINE: PREDICTORS OF MOTIVATION AMONG LONG DISTANCE ELITE RUNNERS (EXPLORING SPORTSPSYCHOLOGY) - Tablizo, Alicia Q; Biado, Diana; Crispino, Hope S; Lee, Mikee Avon; Kemboi, Patrober (PEOPLE: International Journal of Social Sciences, 2018)
This study sought to determine what factors cause the motivation of long distance elite runners in marathons, whether intrinsic motivation or extrinsic motivation. The study utilized a descriptive method in determining if age, gender, and years of running are predictors of motivation among the respondents. The researchers measured the motivation of the selected respondents through a standard questionnaire called the Sports Motivation Scale developed by Pelletier, et. al. (2012). The participants were asked to fill out the questionnaire after the marathon event. The data gathered was analyzed and interpreted using IBM SPSS version 20. As shown in the results, the age, gender, and years of running have no significance with intrinsic motivation. Similar to extrinsic motivation, the age and gender have no significance. However, there is significance between the years of running and extrinsic motivation. Therefore, the researchers concluded that long-distance elite runners who have been running for a number of years are more extrinsically motivated. Future researchers and present sports psychologists and educators may use this study as a guide for them to press forward towards sports amelioration.